2008
DOI: 10.1093/annonc/mdn429
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant oral clodronate improves the overall survival of primary breast cancer patients with micrometastases to the bone marrow—a long-term follow-up

Abstract: These long-term survival data extend the survival advantage reported in previous studies with oral clodronate in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
130
1
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(143 citation statements)
references
References 18 publications
3
130
1
9
Order By: Relevance
“…Bone metastasis-free survival and nonskeletal-free survival were most favorable for clodronate in the Diel et al study, less favorable in the Powles et al study, and unfavorable in the Saarto et al study. Similarly, for patients on clodronate, overall survival was considerably improved for the Diel et al study (HR0.50, P = 0.049), 124 was improved in the Powles et al study (HR 0.74, P = 0.041), 125 and was worse in the Saarto et al study (HR 1.33, P = 0.13). 123 The discrepancy in these trials may be explained by variability in sample size, study populations, and study methodology.…”
Section: Clinical Evidence In Adjuvant Breast Cancer Trialsmentioning
confidence: 84%
“…Bone metastasis-free survival and nonskeletal-free survival were most favorable for clodronate in the Diel et al study, less favorable in the Powles et al study, and unfavorable in the Saarto et al study. Similarly, for patients on clodronate, overall survival was considerably improved for the Diel et al study (HR0.50, P = 0.049), 124 was improved in the Powles et al study (HR 0.74, P = 0.041), 125 and was worse in the Saarto et al study (HR 1.33, P = 0.13). 123 The discrepancy in these trials may be explained by variability in sample size, study populations, and study methodology.…”
Section: Clinical Evidence In Adjuvant Breast Cancer Trialsmentioning
confidence: 84%
“…The studies have reported mixed results, with 445 NCCN Guidelines Insights CE variable effects on DFS and OS. [54][55][56][57] However, in the National Surgical Adjuvant Breast and Bowel Project (NSABP) B-34 trial, although DFS was similar in older and younger women, improvements in skeletal metastasis-free interval (P=.027) and nonskeletal metastasis-free interval (P=.014) were noted with adjuvant clodronate in women >50 years of age. 57 Patients aged >60 years appeared to derive the most benefit from adjuvant clodronate, including an almost 60% reduction in skeletal metastases and a 40% to 50% reduction in nonskeletal metastases.…”
Section: Bisphosphonatesmentioning
confidence: 99%
“…55,56 Several studies confirmed their efficacy in prophylaxis of bone metastasis and their positive impact on survival in selected subgroups of patients. 57 In vitro bisphosphonates were shown to influence the microenvironment by altered secretion of growth factors and cytokines; inhibit tumor cell adhesion, invasion, and proliferation; and induce apoptosis. 58 Furthermore, these drugs may act indirectly on cancer cells through microenvironmental changes using immunomodulatory and antiangiogenic effects.…”
Section: Targeting the Microenvironmentmentioning
confidence: 99%